Medellín, cincuenta años: Iglesia y signos de los tiempos Lectio inauguralis (2018)
The First Congress of Latin American and Caribbean Theology intends to reflect on the conclusive document of the II General Conference of the Latin American Episcopate fifty years after its promulgation, inviting new generations of theologians to reappropriate the meaning of this event in which the Latin American episcopate applied to its own context the category Signs of the times proposed by the Second Vatican Council: a context characterized by a growing awareness of the particularities of the Latin American Church, popular Catholicism, the development of grassroots communities and the urgent need for human promotion and of an effective option for the poor.